Instytucje wspierające rozwój działalności gospodarczej na obszarach wiejskich - Kołodziejczyk, Danuta (Supporting Institutions of Economic Development in Rural Areas, 2006)
The paper presents the supporting institutions of economic development in rural areas. Particular attention is paid to define institution, which means: institutional environment, organizations and mechanisms of its functioning. The paper also shows the importance of their functioning in economy of rural areas.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 441-446